1996
DOI: 10.3950/jibiinkoka.99.653
|View full text |Cite
|
Sign up to set email alerts
|

Patency of the Ostium of the Frontal Sinus After Endoscopic Endonasal Surgery for Chronic Sinusitis

Abstract: We examined the patency of the ostium of the frontal sinus after endoscopic endonasal surgery for chronic sinusitis. This study involved one hundred and seventy-two nasal sides of ninety cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The success rate observed herein is comparable to that of several large series with similar length of follow‐up, and others have noted increased failure rate in more diseased sinuses 10–12 . These studies have recently been reviewed by Weber et al 13 The present study demonstrates that with appropriate medical management and postoperative care, endoscopic frontal sinusotomy can achieve a high success rate despite a significant prevalence of asthma, diffuse polyposis, and failed previous ESS.…”
Section: Discussionsupporting
confidence: 82%
“…The success rate observed herein is comparable to that of several large series with similar length of follow‐up, and others have noted increased failure rate in more diseased sinuses 10–12 . These studies have recently been reviewed by Weber et al 13 The present study demonstrates that with appropriate medical management and postoperative care, endoscopic frontal sinusotomy can achieve a high success rate despite a significant prevalence of asthma, diffuse polyposis, and failed previous ESS.…”
Section: Discussionsupporting
confidence: 82%
“…Tables III and IV summarize the authors previously published and now updated results, and those of others for type I to III sinusotomy. 1–14,47–53 Despite the difficulty in comparing data because of different indications for surgery, different follow‐up times and methods, it seems to be obvious that a bigger drainage procedure leads to a greater probability of an endoscopically open frontal sinus neo‐ostium.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In the frontal sinus recess, revision rates are typically even higher, ranging from 10% to 30%. [16][17][18][19][20][21][22] In these numerous studies reported, there is little attempt to com-pare disorders and match for severity of disease. Although there were observational data about revision, there was no attempt to match severity of disease.…”
Section: Discussionmentioning
confidence: 99%